Struktur, Dynamik und Bedeutung des antarktischen Wasserringes - Fahrbach, Eberhard; Rohardt, Gerd; Strass, Volker; Hellmer, Hartmut (Wissenschaftl. Auswertungen, 2014)
The Southern Ocean plays an important role in the global climate system. The circulation is dominated by the Antarctic Circumpolar Current, which continuously flows from west to east around the Antarctic continent, controlling the exchange of water masses between the Pacific, Atlantic, and Indian Oceans. Superimposed on this zonal current is a meridional overturning circulation that is driven by the divergence of the large-scale wind field. Part of the deep water, which ascends in the Antarctic Divergence, descends to a maximum depth of 1000 m as it flows north. On this level it travels to lower latitudes as Antarctic Intermediate Water. The other part is advected southward within the sub-polar gyres that fill the Ross Sea and the Weddell Sea to the Antarctic marginal seas, where it contributes to the melting of ice and the formation of new water masses. Enhanced heat loss to the atmosphere, interaction with the fringing ice shelves, and salinity increase through the formation of sea ice, creates high-density shelf water, which descends to great depth along the continental slope. The bottom water masses escape from the sub-polar basins through gaps in the confining mid-ocean ridges, cross the Antarctic Circumpolar Current guided by topography, and finally contribute to the ventilation of the World Ocean abyss. All these processes occur on different spatial scales and are subject to large temporal variations. Time series data collected during the last decades have revealed changes in Southern Ocean properties. However, it still has to be clarified whether these changes represent long-term climatic trends or natural interannual to multidecadel variability.